In situ growth of CuO submicro-sheets on optimized Cu foam to induce uniform Li deposition and stripping for stable Li metal batteries. (10th April 2020) - Jiang, Yunpeng; Wang, Bo; Liu, Anmin; Song, Rensheng; Bao, Changyuan; Ning, Yu; Wang, Fei; Ruan, Tingting; Wang, Dianlong; Zhou, Yu
Abstract: Many modifications of matrixes and hosts (e.g., Cu foil or Cu foam) have been used to solve the dendrite problem of Li metal anodes, but most of them neglect the effect of the properties for the current collector itself. In this work, the performance of Cu foam as Li deposition scaffold with different sizes (e.g., thickness and pore density) were compared. By contrast, the blank Cu foam with 1.6 mm thickness and 100 pores per liner inch has been demonstrated with the best performance (96.1% of Coulombic efficiency after 130 cycles at 5 mA/cm 2 for 1 mAh/cm 2 of Li), which is selected as the optimized sample for further modification to solve its dendrite problems. A facile water bath method was used to treat Cu foam for in situ growth of the CuO submicro-sheets on the three-dimensional (3D) skeletons with good electronic contact between the conductive (Cu foam) and lithiophilic (CuO) component. The 3D hierarchical structure not only ensures good lithophilic properties to induce uniform Li nucleation and deposition, but also reduces the real current density, which is beneficial to reduce the polarization of Li deposition. The electrochemical test results demonstrate the high Coulombic efficiencies of 96.5% (135 cycles), 97.5% (230 cycles) and 98.6% (450 cycles) with the current densities of 10 mA/cm 2, 5 mA/cm 2 and 1 mA/cm 2, respectively. Moreover, the presented in-situ growth method is simple, cost-effective, and suitable for large-scale production. In addition, we pointed out the deficiencies of the proposed substrate, proposing that other strategies such as electrolyte modification and SEI modification are still needed to work together to further improve the overall performance of Li metal anode. Graphical abstract: A 3D hierarchical structured Cu foam in situ growth with CuO submicro-sheets was constructed and used as substrate for uniform Li deposition, which exhibited high Coulombic efficiency and superior electrochemical performance for both symmetric and full cells. Image 1 Highlights: A 3D hierarchical structured lithiophilic CuO submicro-sheets was constructed. Uniform Li deposition and Li stripping was obtained on the CuO substrate. High Coulombic efficiency, high current density and long lifespan were achieved. The full cell exhibited improved rate performance and cyclic stability. The deficiencies of the proposed CuO substrate were discussed.